“Procedimento de produção antecipada de provas e arbitragem: panorama brasileiro e análise jurisprudencial do TJSP e STJ” - Poluhoff, Antonio Borisovich de Aguiar (2024)
The aim of this paper is to analyze the dynamics between the Anticipated Production of Evidence procedure and arbitration in the Brazilian legal context, from the perspective of the 2015 Code of Civil Procedure and the Arbitration Law. The study addresses the precautionary nature of the early production of evidence and its implications in the arbitral context, before the Arbitral Tribunal is established, as well as the non-urgent hypotheses, in which there is no formally constituted dispute. The research focuses on how the Anticipated Production of Evidence, provided for in the CPC/15, contributes to guaranteeing rights and ensuring the effectiveness of evidence, analyzing the legislation and doctrine that deal with the relationship between arbitration and the procedure for the production of evidence and its impacts on the stabilization of the claim. To this end, the study examines both decisions of the Superior Court of Justice and the São Paulo Court of Justice, which address the compatibility between PAP and arbitration, as well as the implications of using this mechanism in Brazilian law, and the majority understanding of Brazilian doctrine